2020
DOI: 10.1177/1526602820908056
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Peripheral Vascular Interventions via Retrograde Pedal Access for Chronic Limb-Threatening Ischemia in a Multicenter Registry

Abstract: Purpose: To describe the use and 1-year outcomes of retrograde pedal access during peripheral vascular interventions (PVI) for chronic limb-threatening ischemia (CLTI). Materials and Methods: From October 2016 to September 2017, 159 patients (mean age 71±10 years; 112 men) undergoing PVI via retrograde pedal access were enrolled in the multicenter Vascular Quality Initiative (VQI) registry. The pedal access approach included retrograde femoral (40%), antegrade femoral (26%), retrograde to antegrade femoral (22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The total number of complications (7.6%) was low and mainly related to the access site. In general, this number is similar to previously published data reporting rates of access site complications of up to 13% [14,[31][32][33]. The additional distal access did not increase the number of serious adverse complications (SAR) as only one case suffered from compartment syndrome requiring surgery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The total number of complications (7.6%) was low and mainly related to the access site. In general, this number is similar to previously published data reporting rates of access site complications of up to 13% [14,[31][32][33]. The additional distal access did not increase the number of serious adverse complications (SAR) as only one case suffered from compartment syndrome requiring surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Among a growing number of dedicated devices for CTO revascularization [5,6], a retrograde approach with tibiopedal access is an increasingly used strategy [5,7]. Since its first usage, the techniques and dedicated material have improved, and technical success rates from 80% up to 100% for lesion crossing have been reported [8][9][10][11][12][13][14]. The application of this technique has been expanded to patients with lifestyle-altering claudication (Rutherford stage III) accompanied by an increase in the technical success rates of treatment [8,9,15].…”
Section: Introductionmentioning
confidence: 99%
“…25,36 The six month survival rate, reported by five studies, was estimated to be 91% (95% CI 80%e98%) of 345 patients. 14,20,25,31,39 During a 12 month follow up, the primary patency rate was 62% (three studies; 95% CI 25%e 93%), 18e20 the TLR rate was 33% (four studies; 95% CI 14%e55%), 13,14,18,32 the limb salvage rate was 82% (seven studies; 95% CI 67%e93%), 20,29,31,32,36,39,41 while major amputations were required in 20% (13 studies; 95% CI 13%e28%) of the patients. 13,14,17,18,20,23,25,29,31,32,36,39,41 One study investigating 40 patients reported an additional 15 minor amputations 12 months after the index procedure.…”
Section: Long Term Outcomesmentioning
confidence: 99%
“…Weight -% Zhuang 2020 14 Perry 2020 13 Lai 2019 16 Schmidt 2019 18 Palena 2018 19 Stern 2018 20 Matsumi 2017 23 Affonso 2016 24 Goltz 2016 25 Hanna 2016 26 Tay 2016 29 Walker 2016 30 Sabri 2015 31 Palena 2013 36 Ruzsa 2013 37 Yeh 2011 38 Spinosa 2005 40 Botti anterior tibial and the dorsalis pedis arteries. Distal arterial access and retrograde crossing was achieved in 96% of the cases, while procedural success was 91%, with only a few peri-procedural angiographic complications.…”
Section: Study Es (95% Ci) Technical Successmentioning
confidence: 99%
“…It is our policy, in order to consider the latter access, that all other methods of revascularization (such as the Sub-Intimal Arterial Flossing with Antegrade-Retrograde Intervention-SAFARI-or the Controlled Antegrade and Retrograde Tracking and Dissection-CART-techniques) need to be exhausted due to the fearing of such complications. In the recent multi-center registry analysis on this topic, Perry and colleagues 14 showed that complications were rare and not significantly different between groin versus pedal access groups, including local hematoma and vessel thrombosis. The rates of major adverse limb events at 1 year were higher after pedal access, but the amputation free survival was similar, possibly, as stated by those authors, the result of a trade off between limb salvage and repeated interventions.…”
Section: Discussionmentioning
confidence: 99%